Introducing Pharmacogenetics and Personalized Medicine via a Weblog - Kaitlin Bova; Sara Bova; Kevin Hill; Mark Dixon; Diana Ivankovich; David F. Kisor (University of Minnesota Libraries Publishing, 2014)
Objectives: To evaluate a weblog (blog)-based course introducing pharmacogenetics (PGt) and personalized medicine (PM) relative to freshmen pharmacy students' knowledge base. Methods: Incoming freshmen pharmacy students were invited by email to enroll in a one semester-hour, elective, on-line blog-based course entitled "Personal Genome Evaluation". The course was offered during the students' first semester in college. A topic list related to PGt and PM was developed by a group of faculty with topics being presented via the blog once or twice weekly through week 14 of the 15 week semester. A pre-course and post-course survey was sent to the students to compare their knowledge base relative to general information, drug response related to PGt, and PM. Results: Fifty-one freshmen pharmacy students enrolled in the course and completed the pre-course survey and 49 of the 51 students completed the post-course survey. There was an increase in the students' general, PGt and PM knowledge base as evidenced by a statistically significant higher number of correct responses for 17 of 21 questions on the post-course survey as compared to the pre-course survey. Notably, following the course, students had an increased knowledge base relative to "genetic privacy", drug dosing based on metabolizer phenotype, and the breadth of PM, among other specific points. Conclusions: The study indicated that introducing PGt and PM via a blog format was feasible, increasing the students' knowledge of these emerging areas. The blog format is easily transferable and can be adopted by colleges/schools to introduce PGt and PM.   Type: Case Study